The Influence of Products and Promotions on Consumer Decisions to Study at the Sampit College of Economics - Hendry Yono, Elia; Riassy Christa, Usup; Sambung, Roby (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study aims to determine the Influence of Products and Promotions on Consumer Decisions, Faculty of Economics and Business, University of Palangkaraya. This study aims to determine and analyze the influence of Promotions and Products on Consumer Decisions at the Sampit College of Economics, the sampling technique in this study uses Random Sampling techniques carried out through Observation and Questionnaires. The number of sample sizes taken is 80 samples which are students of the Sampit College of Economics class of 2023. The analysis tool used is SemPLS 4.0. The results of this study indicate that Promotions and Products have a positive and significant influence on Consumer Decisions at the Sampit College of Economics.